Renal Amyloidosis In Pakistan - Ali, Akhtar; Zaidi, Naveed Abbas; Khan, Arbab Nisar; Akhtar, Sultan Zafar (Journal of Postgraduate Medical Institute, 2011)
Summary Renal Amyloidosis is one of the important causes of refractory nephrotic syndrome. A study on renal amyloidosis was performed in Nephrology department of Lady Reading Hospital, Postgraduate Medical Institute Peshawar and extended from Jannuary 1991 to july 1998. The aim of the study was to know the incidence, aetiology, clinical presentation, therapeutic options and clinical outcome of renal amyloidosis.All patients who presented with significant protecinuria or nephortic syndrome with or without hypertension, renal insufficiency or active urinary sediment underwent percutaenous kidney biopsy. The diagnosis of renal amyloidosis was confirmed by classical congo red staining and apple green birefringenece on polarized microscopy. During the period of 8.7 years 80 cases of renal amyloidosis were recognized. Secondary renal amyloidosis was seen more common than the primary one with slight male predominance. Primary renal amyloidosis could not be suspected clinically and was diagnosed retrospectively after renal biopsy. Conversely, secondary renal amyloidosis was anticipated clinically due to associated underlying pathologies. Pulmonary tuberculosis, Bronchiectasis, Chronic Osteomyelitis and Rheumatoid Arthritis were found as the most common causes of secondary renal amyloidosis. This study highlights that renal amyloidosis is not a rare disease but freqeuntly seen in clinical practice as one of the causes of steroid resistant nephrotic syndrome.